Muon-spin relaxation study of charge carrier dynamics in the conducting polymer PPV - Blundell, S; Pratt, F; Marshall, I; Husmann, A; Hayes, W; Martin, R; Holmes, AB (2001)
Muon-spin relaxation (mu SR) experiments on the conducting polymer poly(2,3-dibutoxy-1,4-phenylene vinylene) (DB-PPV) probe the dynamics of the highly mobile polarons created by the muon-implantation process in which muonium reacts with the polymer forming a radical state. The fluctuating spin density induced by the electronic spin defect rapidly diffusing up and down the chain leads to a characteristic relaxation, the temperature and field dependence of which permit the extraction of on-chain and inter-chain diffusion rates. These results provide information concerning: the charge-transport mechanism in DB-PPV.